A prospective analysis of concentration of 25-OHD between northern and southern district in Japan in year-round study. Issue 43 (28th October 2022) - Horikawa, Akira; Kasukawa, Yuji; Hongo, Michio; Kodama, Hiroyuki; Sano, Akihisa; Miyakoshi, Naohisa
Abstract : Although osteoporotic patients have already been recognized as having a low-volume vitamin D status, the concentration of active vitamin D precursor has not been studied in detail. This trial aimed to clarify the concentration of 25-hydroxyvitamin D (25-OHD), which is a natural type of vitamin D and compare between 2 separate areas in Japan. To compare and clarify the concentration of 25-OHD between 2 separate areas, Japanese patients who were diagnosed as having osteoporosis based on bone mineral density were studied. We analyzed 2 different hospitals' patients whose residence is separated into a northern district (Akita city: north latitude 39" 43') and a southern district (Shizuoka city: north latitude 34" 58'). Both of them have completely different daylight hours. Three-hundred sixty eight patients (174 in Akita, 194 in Shizuoka) were enrolled in this trial to compare the differences of concentration of 25-OHD by Welch's t t -test. There were significant differences in the concentration of 25-OHD and age between them. Akita patients were significantly higher than that of Shizuoka patients despite Shizuoka having much daylight hours of Akita. In conclusion, there might be no relationship between the concentration of 25 OHD and exposure to sunlight.